Gestión del talento humana en la empresa de Comida Rápida Times Eat Wing en la ciudad de Guayaquil - Delgado Valenzuela, Jeniffer Andrea (2021)
The area of human talent of the organization, several issues have been raised related to the management of human resources of the organization, due to the current mismanagement, conflicts have arisen among the collaborators of the organization. The organization is being affected by not having established a mission to the organization so the collaborators do not compromise and at the same time do not understand the objectives they want to achieve as a company, in addition to being affected productivity not by collaborators but because the organization itself creates obstacles. An indefinite organizational structure within the organization will not help to achieve the sustainable development of the company. The lack of order and structure of the system is a weakness that directly affects the processes related to the production and delivery time of orders. The selection process adopted by the organization is completed on the basis of the applicant’s curriculum vitae to fill the posts to be filled. Supervisors and managers then select the most suitable candidate in the portfolio to join the company. The selection decision is based on the recruitment of persons with no work experience between 18 and 20 years or recommended workers. In the long run, overworked employees will reduce productivity and increase costs. Because workers are tired and perform poorly, and in the medium to long term, it is not uncommon for them to get sick, which causes them to miss work without warning. The employer must therefore cover all or part of the cost of his paid leave.